Assessing Physico-Chemical Parameters of Drinking Water in Majkhola, Tansen, Palpa - Karki, Deepa; Thapa, Yub Narayan (International Journal of Applied Sciences and Biotechnology, 2022)
Water is an important component of the ecosystem that sustains life on the planet since water provides vital components for human health. To gain a precise picture of water quality, studies of the components found in the water are critical. Three physical and six chemical criteria were examined to assess the quality assurance of drinking water of Majkhola. All tests were carried out according to the protocols outlined in the standard methodology. For this investigation, four water samples were collected in the morning from different areas of Majhkhola throughout three months, from December 2018 to February 2019. The purpose of this study was to evaluate the water quality parameters. pH (6.85 – 8.5), Conductivity (72.3 – 79.9 µm/s), Alkalinity (37.84 – 39.27 mg/L), Chloride (2.509 – 3.76 mg/L), Dissolves Oxygen (DO) (0.8 – 1.3 mg/L), Hardness (60 – 72 mg/L) and Total Dissolved Solids (100 – 150 mg/L) of water samples values lay within the permissible guideline values as prescribed by WHO and national standard but temperature (18 – 21°C) of water samples crossed the WHO permissible value and there is no prescribed limit of free CO2 (2 – 4) mg/L) in WHO. These metrics' values in the research area suggest that water samples are within normal or acceptable limits. As a result, water is safe to drink and meets local and international physical and chemical criteria to preserve excellent health. Based on the findings, it was concluded that the current study's findings are highly encouraging and reflect the health status of Majkhola's water area.Int. J. Appl. Sci. Biotechnol. Vol 10(1): 60-70.